Synthesis of N-[3-(prop-1-yn-1-yl)phenyl] benzene sulfonamide and Determination of its Antibacterial Activity - Cabezas Pizarro, Jorge A. (2019)
The synthesis of N-[3-(prop-1-yn-1-yl)phenyl] benzenesulfonamide was performed and its antibacterial activity against Staphylococcus aureus and Escherichia coli was determined. Minimalinhibitory concentrations (MIC) of 12.5 µg/mL and 25.0 µg/mL were obtained respectively.